Association Between the Use of Tobacco Products and Food Insecurity Among South Korean Adults - Seo Young Kang; Hong-Jun Cho (Frontiers Media S.A., 2022)
Objectives: Food insecurity is the most basic form of human deprivation; thus, strategies to eradicate poverty should include policies to improve food insecurity. This study investigated the association between the use of tobacco products and food insecurity.Methods: We analyzed 21,063 adults from the Korea National Health and Nutrition Examination Survey, 2013-2015, 2019. The OR and 95% CI for food insecurity was calculated in each category of the status of tobacco products use and sociodemographic characteristics using multivariable logistic regression analysis.Results: Of 21,063 participants, 7.3% belonged to the food insecurity group. The OR (95% CI) for food insecurity was 1.34 (1.08-1.65) among current users of any tobacco products compared with those who had never used any tobacco product. The odds for food insecurity were higher among those with secondhand smoke exposure, younger participants, those with lower household income, lower levels of education, manual workers or people without occupation, and separated/widowed/divorced participants.Conclusion: Use of any tobacco products was associated with food insecurity among South Korean adults. Tobacco control could improve food insecurity.